Early recurrence in paroxysmal versus sustained atrial fibrillation in patients with acute ischaemic stroke. (March 2019) - Paciaroni, Maurizio; Angelini, Filippo; Agnelli, Giancarlo; Tsivgoulis, Georgios; Furie, Karen L; Tadi, Prasanna; Becattini, Cecilia; Falocci, Nicola; Zedde, Marialuisa; Abdul-Rahim, Azmil H; Lees, Kennedy R; Alberti, Andrea; et al.
Background: The relationship between different patterns of atrial fibrillation and early recurrence after an acute ischaemic stroke is unclear. Purpose: In a prospective cohort study, we evaluated the rates of early ischaemic recurrence after an acute ischaemic stroke in patients with paroxysmal atrial fibrillation or sustained atrial fibrillation which included persistent and permanent atrial fibrillation. Methods: In patients with acute ischaemic stroke, atrial fibrillation was categorised as paroxysmal atrial fibrillation or sustained atrial fibrillation. Ischaemic recurrences were the composite of ischaemic stroke, transient ischaemic attack and symptomatic systemic embolism occurring within 90 days from acute index stroke. Results: A total of 2150 patients (1155 females, 53.7%) were enrolled: 930 (43.3%) had paroxysmal atrial fibrillation and 1220 (56.7%) sustained atrial fibrillation. During the 90-day follow-up, 111 ischaemic recurrences were observed in 107 patients: 31 in patients with paroxysmal atrial fibrillation (3.3%) and 76 with sustained atrial fibrillation (6.2%) (hazard ratio (HR) 1.86 (95% CI 1.24–2.81)). Patients with sustained atrial fibrillation were on average older, more likely to have diabetes mellitus, hypertension, history of stroke/ transient ischaemic attack, congestive heart failure, atrial enlargement, high baseline NIHSS-score and implanted pacemaker. After adjustment by Cox proportional hazard model, sustained atrial fibrillation was not associated with early ischaemic recurrences (adjusted HR 1.23 (95% CI 0.74–2.04)). Conclusions: After acute ischaemic stroke, patients with sustained atrial fibrillation had a higher rate of early ischaemic recurrence than patients with paroxysmal atrial fibrillation. After adjustment for relevant risk factors, sustained atrial fibrillation was not associated with a significantly higher risk of recurrence, thus suggesting that the risk profile associated with atrial fibrillation, rather than its pattern, is determinant for recurrence.